Does capital structure mediate the relationship between asset structure and company size on profitability? - Amelia Anja Ristianti; Suwitho Suwitho; Budhi Satrio (University of Merdeka Malang, 2023)
The high value of the capital structure (DAR) among companies in the agricultural sector signifies a greater reliance on debt capital than equity capital. This research aims to examine the influence of asset structure and company size on capital structure, with the mediating role of profitability. The study is based on case studies of agricultural sector companies that became publicly listed during the period 2014-2019. Path analysis is employed as the analytical method. The findings reveal a positive and significant impact of company size on profitability within agricultural sector companies listed on the IDX. Concerning asset structure, company size, and profitability, all three factors display a positive and significant effect on the capital structure of agricultural sector companies listed on the IDX. However, the study determines that profitability does not act as a mediator in the relationship between asset structure and company size concerning the capital structure of agricultural sector companies listed on the IDX.